Effectiveness and Efficiency of the Use of the Workforce Training Program Budget at the North Sumatra Provincial Manpower Office - Novitayana Novitayana; Irawan Irawan (Utan Kayu Publishing, 2025)
This study analyzes the effectiveness and efficiency of budget utilization for workforce training programs at the Manpower Office of North Sumatra Province using a qualitative approach. Although average budget realization reaches 90.60%, graduate employment absorption remains low at 38.9%–56.4%. Data were collected through in-depth interviews with budget officials, instructors, and trainees, as well as document reviews. Findings show that 78% of respondents consider budget implementation administratively compliant, but only 46% believe training materials match industry needs. Additionally, 63% identify limited facilities as the main obstacle to program effectiveness. The study suggests industry-based training planning, improved facilities, and stronger evaluations to optimize budget use